Predicting the optimal solution in fuzzy linear programming problem - Davoodi, S.M.; Abdul Rahman, N.A. (Bulletin of the Karaganda University. Mathematics Series, 2021)
In this paper we try to define a percentage form of LR fuzzy numbers which is a useful form of fuzzy numbers and its’ arithmetics. So, we show how the maximum variation range of optimal value of fuzzy objective function can be predicted by using this form of fuzzy numbers. Since fuzzy problems are generally solved through a complicated manner, the purpose of this study is releasing a kind of prediction for the final solution in the way that the manager can access to an outlook to optimal solution (Z∗) without solving the problem. Finally, optimal value of fuzzy objective function on fuzzy linear programming is predicted whenmaximum variation range of fuzzy variable have been predetermined.